How to design the ask?: Funding units vs. giving money - Diederich, Johannes; Epperson, Raphael; Goeschl, Timo (AWI discussion paper series, 2022)
Unit donations are an alternative fundraising scheme in which potential donors choose how many units of a charitable good to fund, rather than just giving money. Based on evidence from an online experiment with 8,673 participants, we demonstrate that well-designed unit donation schemes can significantly boost giving above and beyond the standard money donation scheme. A decomposition of the underlying mechanisms shows patterns consistent with the conjecture that unit donations increase impact salience and leverage donors' cognitive biases by changing the metric of the donation space. The potential increase in donations likely outweighs the complications of designing a unit scheme, but requires expert handling of the choice of unit sizes.